A niobium and tantalum co-doped perovskite cathode for solid oxide fuel cells operating below 500 °c - Li, M.; Zhao, M.; Li, F.; Zhou, W.; Peterson, V.; Xu, X.; Shao, Zongping; Gentle, I.; Zhu, Z. (Macmillan Publishers Limited, 2017)
The slow activity of cathode materials is one of the most significant barriers to realizing the operation of solid oxide fuel cells below 500 °C. Here we report a niobium and tantalum co-substituted perovskite SrCo0.8Nb0.1Ta0.1O3-d as a cathode, which exhibits high electroactivity. This cathode has an area-specific polarization resistance as low as ~0.16 and ~0.68 Ocm2 in a symmetrical cell and peak power densities of 1.2 and 0.7 W cm-2 in a Gd0.1Ce0.9O1.95-based anode-supported fuel cell at 500 and 450 °C, respectively. The high performance is attributed to an optimal balance of oxygen vacancies, ionic mobility and surface electron transfer as promoted by the synergistic effects of the niobium and tantalum. This work also points to an effective strategy in the design of cathodes for low-temperature solid oxide fuel cells.